Pengaruh Investasi Terhadap Penyerapan Tenaga Kerja pada Sektor Industri Besar di Kabupaten Sidoarjo - Dita Putri Eka Wahyuni; Kukuh Arisetyawan; Lucky Rachmawati; Ladi Wajuba Perdini Fisabilillah (Jurnal Simki Economic, 2024)
One of the classic problems in Indonesia that has not been successfully resolved until now and continues to be scientifically researched is the unemployment rate. This study aims to analyze whether the number of employment in large industries is affected by investment. This research applies quantitative methods and time series data analysis processed with the help of Stata. The research was conducted in one of the provinces in East Java, namely Sidoarjo Regency with a limited range of years between 2010 and 2021. The type of data applied is secondary data obtained through the Sidoarjo Regency Communication and Information Office. The results indicate that investment positively and significantly affects labor absorption. This means that an increase in investment increases labor absorption. The greater the investment, the higher the employment. Suggestions for future researchers are to use a wider scope of research data, such as the scope of Indonesia. In addition, it can expand the category of variables on the effect on educated, trained, uneducated, and unskilled labor.